Corrigendum: Reaching 30% energy coupling efficiency for a high-density-carbon capsule in a gold rugby hohlraum on NIF (2021 Nucl. Fusion64 086028). (13th September 2021) - Ping, Y.; Amendt, P.; Baker, K.; Smalyuk, V.A.; Chen, H.; Khan, S.; Hartouni, E.P.; Ho, D.; Jones, O.; Landen, O.N.; Lemos, N.; Lindl, J.; et al.
Abstract: In the published paper titled 'Reaching 30% energy coupling efficiency for a high-density-carbon capsule in a gold rugby hohlraum on NIF' (2021 Nucl. Fusion 61 086028), the red shaded areas representing experimental uncertainties did not show up in figures 2 and 3 . This corrigendum provides the correct figures 2 and 3 .